Answer:
see explanation
Explanation:
Assuming the equation to be
| 3x - 4 | = 5, then there are 2 possible solutions
3x - 4 = 5 or 3x - 4 = - 5 ( add 4 to both sides of both equations )
3x = 9 or 3x = - 1 ( divide both sides by 3 in both equations )
x = 3 or x = -
![(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o08xg954t1gbzo9avralvfomcybk63rm02.png)
As a check substitute these values into the left side of the equation and if equal to the right side then they are the solutions
x = 3
| 9 - 4 | = | 5 | = 5 ← correct
x = -
![(1)/(3)](https://img.qammunity.org/2020/formulas/mathematics/middle-school/o08xg954t1gbzo9avralvfomcybk63rm02.png)
| - 1 - 4 | = | - 5 | = 5 ← correct